Pengaruh Riwayat Keparahan COVID-19 terhadap TNF-α dan IFN-γ Monosit Pasien Diabetes Melitus Tipe 2 - Wahyurini, Dyahati; Tahapary, Dicky L; Wibowo, Heri (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Monocytes are very sensitive to changes in the metabolic environment, including hyperglycemia, such as type 2 diabetes mellitus (T2DM). T2DM is characterized by chronic low-grade inflammation and becomes one COVID-19 comorbid. TNF-α and IFN-γ are cytokines often linked to inflammation, the severity of COVID-19, and long COVID-19. This study aims to analyze the relationship between COVID-19 severity and TNF-α and IFN-γ in T2DM one month post-infection.Methods: This research is an experimental study at the Integrated Laboratory Faculty of Medicine, Universitas Indonesia, for four months. The total samples are 44 cryotubes of PBMC (18 T2DM and 26 Non-T2DM) from the CARAMEL study (COVID-19, Aging, and Cardiometabolic Risk Factors). PBMCs were stimulated with inactivated whole virions SARS-CoV-2 and incubated for 24 hours. Monocyte subsets and intracellular cytokines are detected by flow cytometry.Results: Research showed that IFN-γ in the T2DM group was higher in all subsets. There was no significant difference between the T2DM and non-T2DM groups. Based on the history of the severity of COVID-19, MedFI IFN-γ classic and intermediate monocytes differed significantly between the COVID-19 severity groups (p = 0.049 and p = 0.022). Further research is needed to analyze the risk factors involved.Conclusion: MedFI of classic and intermediate monocyte IFN-γ differed significantly between the severity of COVID-19. There were no significant differences between the T2DM and non-T2DM groups. The history of the severity of COVID-19 is significantly related to long COVID-19.